2016
DOI: 10.1080/17512549.2016.1174736
|View full text |Cite
|
Sign up to set email alerts
|

Application of building-dynamics-based control strategies to improve air-conditioning performance in educational buildings

Abstract: A comprehensive model was developed to analyse the performance of different air-conditioner (A/C) control strategies of an educational building in a hot summer environment. The main objective of the study was to evaluate thermal performance of the existing A/C control system to identify the causes of uneven temperature profiles in classrooms, and to assess alternative control systems in terms of their ability to achieve thermal comfort as well as optimal levels of energy consumption. The performance of four co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…High energy consumption of air conditioning system is due to the fact that maximum ambient temperature is close to 30 • C during the entire year. Other authors [39][40][41] have also determined that it is the air conditioning system the piece of equipment that consumes most energy within a building. It should also be noted that in the 2006 ED, the categories for computers and air conditioning were responsible for 37% and 15% of energy consumption respectively.…”
Section: Results Of the Rei-unam Surveymentioning
confidence: 99%
“…High energy consumption of air conditioning system is due to the fact that maximum ambient temperature is close to 30 • C during the entire year. Other authors [39][40][41] have also determined that it is the air conditioning system the piece of equipment that consumes most energy within a building. It should also be noted that in the 2006 ED, the categories for computers and air conditioning were responsible for 37% and 15% of energy consumption respectively.…”
Section: Results Of the Rei-unam Surveymentioning
confidence: 99%
“…These quantities depend on factors such as clothing insulation, a person's metabolic rate, relative air velocity and, naturally, the ambient air temperature. In order to circumvent the subjectiveness of both the PMV and PPD indexes, the majority of authors as well as practitioners opt for simply defining temperature envelopes to be respected in each environment [Mantovani and Ferrarini, 2015, Ma et al, 2015, Ben-Nakhi and Mahmoud, 2017. The reader is referred to [Garnier et al, 2014, Garnier et al, 2015, Gupta and Kar, 2018 for exceptions of this tendency.…”
Section: The Goals Of Hvac Systemsmentioning
confidence: 99%
“…With regard to the first aspect, some numerical analyses indicated that energy use could be reduced by choosing appropriate setpoints [5,6]; conversely, the adoption of only one thermostat may be deficient in certain occupancy cases [7,8]. Controller tuning by setpoint regulation often provides relatively low-or no-extra-cost solutions for existing buildings [9].…”
Section: Introductionmentioning
confidence: 99%